2017
DOI: 10.1002/adhm.201700687
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hyaluronic Acid and Glioblastoma Cell Coculture on the Formation of Endothelial Cell Networks in Gelatin Hydrogels

Abstract: Glioblastoma (GBM) is the most common and deadly form of brain cancer. Interactions between GBM cells and vasculature in vivo contribute to poor clinical outcomes, with GBM-induced vessel co-option, regression, and subsequent angiogenesis strongly influencing GBM invasion. Here, elements of the GBM perivascular niche are incorporated into a methacrylamide-functionalized gelatin hydrogel as a means to examine GBM–vessel interactions. The complexity of 3D endothelial cell networks formed from human umbilical vei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 72 publications
(106 reference statements)
4
95
0
Order By: Relevance
“…We have previously demonstrated that endothelial cell networks can be sustained and tuned within gelatin hydrogels using a co-culture and endothelial cells and fibroblasts [40]. We also observed that including U87-MG GBM cells in the culture system leads to close association between GBM cells and the developing endothelial cell networks, followed by dissolution of these networks in a manner reminiscent of co-option [69].…”
Section: Gbm Progression Is Believed To Be Linked To the Interactionsmentioning
confidence: 87%
See 3 more Smart Citations
“…We have previously demonstrated that endothelial cell networks can be sustained and tuned within gelatin hydrogels using a co-culture and endothelial cells and fibroblasts [40]. We also observed that including U87-MG GBM cells in the culture system leads to close association between GBM cells and the developing endothelial cell networks, followed by dissolution of these networks in a manner reminiscent of co-option [69].…”
Section: Gbm Progression Is Believed To Be Linked To the Interactionsmentioning
confidence: 87%
“…Lithium acylphosphinate (LAP) was added as a photoinitiator at 0.1% w/v for GelMA-only gels and 0.02% w/v for GelMA/HAMA gels. The reduced photoinitiator concentration allowed for equivalent elastic moduli (~3 kPa) between the GelMA and GelMA + HA constructs [40]. Cell seeded hydrogels (GelMA only; GelMA+HA) were then formed in one of three configurations: GBM-only; Perivascular-only; or Tri-Culture.…”
Section: Fabrication Of Cell Seeded Gelatin Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using such integrated systems, microenvironmental adaptation was observed during GBM invasion (Cha et al, 2016); changes in the GBM invasion of the HA matrices were mediated by the focal adhesion kinase and MMP, within the fibrous structures, in response to blockade of a HA-mediated pathway of GBM invasion. Recently, other cellular components in the microenvironment were incorporated into 3D GBM models, revealing the roles of glial cells and the perivascular niche in GBM invasion (Grodecki et al, 2015;Iwadate et al, 2016;Gritsenko et al, 2017;Ngo and Harley, 2017).…”
Section: Hybrid Scaffolds For Gbm Microenvironmentmentioning
confidence: 99%